2019
DOI: 10.1097/md.0000000000013872
|View full text |Cite
|
Sign up to set email alerts
|

Migration of an intrauterine device causing severe hydronephrosis progressing to renal failure

Abstract: Rationale:Intrauterine device (IUD) is commonly used in China. Its complications include uterine perforation, IUD ectopic migration, etc. However, a migrated IUD rarely leads to renal failure.Patient concerns:IUD insertion in the patient was followed by unexplained pain in the left renal area, without bladder irritation or dysuresia.Diagnoses:Hydronephrosis, renal failure, migrated IUD.Interventions:The patient underwent laparoscopic and retroperitoneoscopic left nephrectomy, partial ureterectomy, and migrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Li et al reported a laparoscopic left nephroureterectomy for a nonfunctioning kidney after lodging an intrauterine contraceptive device in the left distal ureter for 3 years. 11 Case reports by Sener et al 1 and Miraliakbari et al 5 demonstrated segmental ureterectomy of the stenotic segment along with ureteroneocystostomy and removal of the foreign objects. Chen et al 9 showed a failed ureteroscopy followed by spontaneous passage of an endoscopic glue material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al reported a laparoscopic left nephroureterectomy for a nonfunctioning kidney after lodging an intrauterine contraceptive device in the left distal ureter for 3 years. 11 Case reports by Sener et al 1 and Miraliakbari et al 5 demonstrated segmental ureterectomy of the stenotic segment along with ureteroneocystostomy and removal of the foreign objects. Chen et al 9 showed a failed ureteroscopy followed by spontaneous passage of an endoscopic glue material.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Migration or erosion of suture materials, mesh, Hemo-Lok clips, metallic clips, vascular graft materials, coils used for embolization, guidewire introducer, suprapubic catheter, intrauterine contraceptive device into the ureters have been reported in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13] In some clinical scenarios, symptoms such as flank pain, urinary tract infections, and lower urinary tract symptoms (frequency, hematuria, and dysuria) may be an indication for a foreign body erosion into the urinary tract. 3,4,9 extraction of such foreign bodies may also depend on the anatomical location, size, shape, and mobility of the object.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is no known reason for the patient's urethral injury, making this a case of truly spontaneous rupture. Any conclusion based upon available studies and history would be purely speculative [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Other unusual sites of IUD migration have been reported, including bladder, ureter, and inguinal region. [ 8 , 18 , 19 ] Patients can be asymptomatic or have serious complications, such as fistulas, intra-abdominal abscesses, intestinal perforations or renal failure. [ 13 , 18 , 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%